Pelatihan dan Monitoring Pemanfaatan Literasi Media Digital di Masa Pandemi Covid 19 bagi Guru di Gugus 2 Kecamatan Pagelaran Kabupaten Malang - Dwi Setiawan; Farida Nur Kumala (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Digital media literacy and monitoring the use of digital media and online media during the COVID-19 pandemic are currently widely accessed by the general public, but many students during the current pandemic are not able to use digital media intelligently. The objectives of this community service activity include: 1) providing education and socialization to teachers and parents about the characteristics of digital media accessed by children during the COVID-19 pandemic, 2) providing knowledge about the impact of using digital media on behavior and development. psychology of children, 3) provide encouragement to teachers and parents to be able to provide assistance to children in managing the use of digital media intelligently. This type of service design is socialization and case studies as well as the method in carrying out this activity using the question and answer method of training, lectures, discussions, and case simulations about the use of gadgets that are good and right. The method used in community service is through seminar kits and workshops. With these trainings and workshops, it is hoped that there will be two-way communication, both between resource persons and participants and between participants themselves. The results of the training activities during mentoring for approximately 1 month are: 1) teachers are more interactive when teaching online in packaging learning using applications that are synchronized with online media such as zoom meetings, google meetings and group watzhap. 2) Parents and teachers are increasingly understanding about the characteristics of digital media, 3) teachers and parents are increasingly understanding about the impact of using digital media on children's behavior and psychological development, 4) parents are increasingly effective in assisting children in regulating intelligent use of digital media anytime and anywhere, 5) there is a very big influence that students are motivated to be enthusiastic in learning because during this pandemic there is a scale of restrictions in learning, 6) There is awareness of parents in preparing financially to buy learning quota packages maximum.